EVALUASI PENINGKATAN LAYANAN SISTEM INFORMASI AKADEMIK PADA IBI DARMAJAYA BANDAR LAMPUNG MENGGUNAKAN FRAMEWORK COBIT 4.1 - -, Indera; Irianto, Suhendro Yusuf (244-5567)
The usage of Information technology in education institution needs good management. Information technology audit is a correlation structure and a process to guide and control of education institution in reaching out the goal by adding of the value and balancing the risk toward information technology and the processes, information technology audit covers the planning process, implementation and evaluation. In audit information technology implementation, in order to the applying can be done maximally, it needs a good planning and implementation otherwise the control must be done continuously, so the applying of information technology audit will be in accordance with education institutionâs vision and mission. Reaching the whole ones need goodÂ  management and arrangement system (IT Governance).The evaluation toward management and arrangement can be used any kind of methods, one of is using COBIT (Control Objectivesfor Information and Relaated Technology). COBIT is a standard model which provides best practice documentation of information technology management which can help management and user in order to bridge of discrepancy between business risks, control needs, technical problems.This research used COBIT framework to know information technologyâs maturity level in IBI Darmajaya so it can made the strategy to increase academic information system service quality (SIAKAD) in IBI Darmajaya.Â Â Â Â Key Word :Â  Information Technology Audit, COBIT, Academic Information System